Teaching preschool children to report suspicious packages to adults. Issue 3 (16th May 2018) - May, Michael E.; Shayter, Ashley M.; Schmick, Ayla; Barron, Becky; Doherty, Meghan; Johnson, Matthew
Abstract : Law enforcement agencies stress that public reporting of terror‐related crime is the predominant means for disrupting these actions. However, schools may be unprepared because the majority of the populace may not understand the threat of suspicious materials or what to do when they are found on school grounds. The purpose of this study was to systematically teach preschool children to identify and report suspicious packages across three experiments. In the first experiment, we used multiple exemplar training to teach children to identify the characteristics of safe and unsafe packages. In the second experiment, we taught participants to identify the locations where packages should be considered unsafe. Finally, in the third experiment, we used behavioral skills training to teach participants to avoid touching unsafe packages, leave the area where they were located, and report their discovery to an adult. Results suggest the participants quickly developed these skills. Implications for safety skills in young school children are discussed.